2016
DOI: 10.1002/nbm.3576
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging and histology of developing hearts

Abstract: Diffusion tensor imaging (DTI) has emerged as a promising method for noninvasive quantification of myocardial microstructure. However, the origin and behavior of DTI measurements during myocardial normal development and remodeling remain poorly understood. In this work, conventional and bicompartmental DTI in addition to three-dimensional histological correlation were performed in a sheep model of myocardial development from third trimester to postnatal 5-months of age. Comparing the earliest time points in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 64 publications
(105 reference statements)
6
14
0
Order By: Relevance
“…The appearance of the absolute sheetlet angle maps in the LV of term lambs (Figure 4) was consistent with previous DTI studies in healthy hearts (Abdullah et al, 2016; Chen et al, 2005; Cheng et al, 2012; Ferreira et al, 2014). The absolute sheetlet angles in the LV of former‐preterm lambs appeared to be reduced, relative to the term‐born lambs, as shown in the sheetlet angle map in Figure 4.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…The appearance of the absolute sheetlet angle maps in the LV of term lambs (Figure 4) was consistent with previous DTI studies in healthy hearts (Abdullah et al, 2016; Chen et al, 2005; Cheng et al, 2012; Ferreira et al, 2014). The absolute sheetlet angles in the LV of former‐preterm lambs appeared to be reduced, relative to the term‐born lambs, as shown in the sheetlet angle map in Figure 4.…”
Section: Resultssupporting
confidence: 89%
“…Normal transmural heterogeneity of fractional anisotropy was seen in the LV, as reported in previous studies (Jiang et al, 2007; McGill et al, 2015); however, no regional differences were found. The fractional anisotropy values in this study are consistent with previous findings in term lambs at 5 months of age (Abdullah et al, 2016). Histologically validated DTI studies of developing prenatal and postnatal hearts have shown that fractional anisotropy changes throughout development, potentially due to changes in cell size and shape (Abdullah et al, 2016; Chen et al, 2005), although the direction in which this change occurs is unclear.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations